Relationship Between the Personal Hygiene and The Occurrence of Pityriasis Versicolor In Students of State Senior High School 1 Medan 2020 - Nasution, Namira Afifah; Hazlianda, Cut Putri (Talenta Publisher, 2024)
Background: Pityriasis versicolor (PV) is a superficial fungal infection on the outermost layer of skin caused by Malassezia furfur or Pityrosporum orbiculare, this infection stays for a long time, mild, and mostly the inflammation affects the face, neck, body, upper arm, axilla, thigh, and groin. PV often found in tropical areas and attack all ages, but mostly found on teenager age between 16-20 years. Self-care maintenance could be done by maintaining the good personal hygiene, because a poor personal hygiene was the risk factor that trigger pityriasis versicolor. This study has an objective to find out whether there is a relationship between personal hygiene and pityriasis versicolor of State Senior High School 1 Medan students in 2020. This study was observational with cross sectional design, the sample for this study were 100 students in State Senior High School 1 Medan in 2020 by using simple random sampling. Data was collected using an online questionnaire. Based on data from chi square method, there is a result value p=0,027 (pâ‰¤0,05). There is a meaningful relationship between personal hygiene and pityriasis versicolor. Â Pendahuluan: Pitiriasis versikolor adalah infeksi jamur superfisial pada lapisan tanduk kulit yang disebabkan oleh Malassezia furfur atau Pityrosporum orbiculare. Infeksi ini bersifat menahun, ringan, dan biasanya tanpa peradangan yang mengenai muka, leher, badan, lengan atas, ketiak, paha, dan lipatan paha. Pitiriasis versikolor banyak dijumpai di daerah tropis dan dapat menyerang semua usia, namun paling banyak pada remaja usia 16-20 tahun. Pemeliharaan perawatan diri dilakukan dengan menjaga higiene perseorangan yang baik karena higiene perseorangan yang buruk adalah faktor yang memicu pitiriasis versikolor Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara higienitas dan pityriasis versicolor pada siswa SMAN 1 tahun 2020. Metode: Penelitian ini merupakan jenis penelitian observasional dengan rancangan cross sectional. Sampel pada penelitian ini siswa-siswi SMAN 1 Medan tahun 2020 sebanyak 100 dan menggunakan metode simple random sampling. Data yang diperoleh melalui pengisian kuesioner secara online. Hasil: Berdasarkan data yang didapati menggunakan motede chi square, didapati hasil nilai p=0,027 (pâ‰¤0,05). Kesimpulan: Terdapat hubungan yang bermakna antara higiene perseorangan dengan kejadian pitiriasis versikolor.